2015
DOI: 10.1080/15533174.2014.988813
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) Complex ofMeso-Tetraphenylporphyrin With 4-Methoxyaniline: Crystal Structure and Antimicrobial Activities of 4-Methoxyaniline-5, 10, 15, 20-Tetraphenyl-Porphyrinatozinc (II)

Abstract: 2015): Zinc(II) complex of meso-tetraphenylporphyrin with 4-methoxyaniline: Crystal structure and antimicrobial activities of 4-methoxyaniline-5, 10, 15, 20-tetraphenyl-porphyrinatozinc (II), Synthesis and Reactivity in Inorganic, Metal-Organic, and Nano-Metal Chemistry, Abstract 4-methoxyaniline-5,10,15,20-tetraphenylporphyrinatozinc(II),[(ZnTPP(MOAN)]1 was synthesized (MOAN = 4-methoxyaniline) and characterised by elemental analysis and spectroscopic techniques. The molecular structure of 1 was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The ZnP modified with methoxy group on meso -phenyl groups displayed activity against Candida albicans fungi. Decoration of ZnP with butyl radical in the third and fourth positions of the pyridine ring increased its antimicrobial activity against Gram-negative and Gram-positive bacteria. , Ravikumar and coauthors reported on SnP activity against Bacillus subtilis and Escherichia coli triggered by direct DNA damage via groove binding . S. Moghnie and co-workers have tested the antifungal properties of Zn (II) cationic meso -tetrakis­( N -alkylpyridinium-2-yl)­porphyrin on Saccharomyces cerevisiae and found that MeP modification in four pyridyl nitrogens of meso positions to six-carbon aliphatic chains significantly increased the PS hydrophilicity and its photoactivity compared to commercially available chlorin e6 …”
Section: Therapymentioning
confidence: 99%
“…The ZnP modified with methoxy group on meso -phenyl groups displayed activity against Candida albicans fungi. Decoration of ZnP with butyl radical in the third and fourth positions of the pyridine ring increased its antimicrobial activity against Gram-negative and Gram-positive bacteria. , Ravikumar and coauthors reported on SnP activity against Bacillus subtilis and Escherichia coli triggered by direct DNA damage via groove binding . S. Moghnie and co-workers have tested the antifungal properties of Zn (II) cationic meso -tetrakis­( N -alkylpyridinium-2-yl)­porphyrin on Saccharomyces cerevisiae and found that MeP modification in four pyridyl nitrogens of meso positions to six-carbon aliphatic chains significantly increased the PS hydrophilicity and its photoactivity compared to commercially available chlorin e6 …”
Section: Therapymentioning
confidence: 99%
“…Nano-building blocks are molecules with specific structures and shapes in nanometer sizes. They can be classified , as one-dimensional (1D) rod-like molecules (such as biphenyl and azobenzene), two-dimensional (2D) disk-like molecules (such as triphenylene and porphyrin ), and three-dimensional (3D) molecules [such as polyhedral oligomeric silsesquioxane (POSS) and fullerene (C60) ] according to their shapes. Unlike BCPs, nano-building blocks often form ordered structures on the sub-10 nm length scale.…”
Section: Introductionmentioning
confidence: 99%